The Eskimo-Aleut Dentition: Crown and Root Morphology - G. Richard Scott (University of Zagreb. School of Dental Medicine, 2020)
Objective of work: This paper provides an overview of crown and root morphology in Eskimo-Aleut populations of the American Arctic. For context, Eskimo-Aleut dental variation is compared to closely related American Indians and distantly related Europeans. Materials and methods: The characterization of dental trait frequency variation is based on observations made on approximately 10,000 dentitions scored by the late Christy G. Turner II and the author. Sixteen crown and five root traits were scored following the conventions outlined in the Arizona State University Dental Anthropology System. Results: Of the 21 dental traits considered, only three showed slight differences among Eskimo- Aleuts, American Indians, and Europeans (UM1 cusp 5, LM2 groove pattern, LM2 root number). For the remaining traits, there was typically a dramatic contrast between the two New World populations and Europeans. While generally similar, Eskimo-Aleuts and American Indians showed differences in UI1 winging, shoveling, and double shoveling, UM1 Carabelli trait, 2-cusped UM2, 3-rooted UM2, and especially 3-rooted LM1. Conclusion: The differences between the three groups are likely a product of genetic drift and founder effect although recent work on the EDAR V370A allele suggests some dental variables like shoveling and lower molar cusp number may indirectly reflect natural selection operating on other variables influenced by this allele.